Application Of Discovery Learning Model To Students' Science Process Skills In Class Vii - Tindiati, Tindiati; Ningsih, Kurnia; Marlina, Reni (Universitas Tanjungpura, 2024)
This study aims to determine the application of the Discovery Learning model to the science process skills (KPS) of students on Environmental Pollution material in class VII SMPN 01 Sanggau Ledo. The form of this research is a pseudo experiment (Quasy Experimental Design) with a research design of nonequivalent control group design. The sampling technique used intact group, class VII A as an experiment and VII B as a control. The instrument used was a multiple-choice test totaling 20 questions and an observation sheet of Science Process Skills (KPS). From the results of the analysis of Science Process Skills (KPS) obtained an average percentage of Science Process Skills (KPS) in the Experimental class of 86.60% with a very good category, and the control class obtained an average percentage of Science Process Skills (KPS) of 75.00% with a good category, this shows that Science Process Skills (KPS) in the experimental class are higher than KPS in the control class.Keywords: Discovery Learning, Science Process Skills, Environmental Pollution